Trauma, Betrayal and the Resistance: a marxist analysis of Ngũgĩ wa Thiong'o’s Weep Not, Child and Matigari - Hussain, Rusafa (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.